Growth and Stability in the Middle East and North Africa - Eken, Sena (Pamphlet Series; Pamphlet Series, No., 1996)
This paper provides an economic overview of the very diverse countries within the large geographical area. It highlights the economic challenges and opportunities facing the MENA region, the policies pursued by the countries in the region, and the outlook for the external environment. The paper concludes with eight policy recommendations.